Quality of drill-based site preparation and early performance of Norway spruce and Scots pine seedlings planted in different seasons - Kemppainen, Kalle; Miina, Jari; Tarvainen, Eetu; Kankaanhuhta, Ville; Laitila, Juha; Peltola, Heli; Strandström, Markus; Kärhä, Kalle (Suomen metsätieteellinen seura, 2026)
Mechanical site preparation (MSP) is essential for successful forest regeneration. However, excessively exposed soil may harm the environment and increase the total costs of seedling stand management. A drill-based MSP device (drill), designed to reduce soil exposure, was recently tested in Finland. This study investigated the quality of drill-based MSP and the early performance of Norway spruce (Picea abies (L.) Karst.) and Scots pine (Pinus sylvestris L.) seedlings planted in different seasons on five mineral soil stands. The findings showed that the mean area of the drilling spots (0.18 m2) was about 20% of that reported for mounding. The drill mostly resulted in good (61%) or satisfactory (34%) planting spot quality (e.g., good spots were covered with mineral soil). Ground and soil obstacles, such as roots, stones, stumps, and logging residues, negatively affected planting spot quality. About 13% of the planting spots did not have a pure mineral soil cover, which is required to mitigate pine weevil (Hylobius abietis L.) damage. Most seedlings were still alive one year after planting, but the proportion of healthy seedlings was 71% for Norway spruce and 48% for Scots pine two years after planting. Overall, drill-based MSP may be most feasible for drier sites with less competitive ground vegetation. However, the productivity and costs, the performance of the planted seedlings, and other potential benefits of drill-based MSP should be further tested under varying operating conditions and compared with those of conventional MSP methods.
Keywords: forest regeneration; seedling survival; manual planting; mechanical soil preparation